Respons Tiga Varietas Kacang Hijau terhadap Aplikasi Pupuk Boron dengan Dosis Bervariasi: Respons Tiga Varietas Kacang Hijau terhadap Aplikasi Pupuk Boron dengan Dosis Bervariasi - Fitriani, Miranti Sari; Arzita; Fathia, Nyimas Myrna Elsa; Nusifera, Sosiawan; Arzita, Arzita (Universitas Bangka Belitung, 2025)
Boron is a micronutrient that plays an important role in plant growth and development. This research aims to determine the response of several varieties to the application of different doses of boron fertilizer and to obtain the best dose for each variety. The experiment was arranged in a randomized block design with a two-factor factorial pattern with two replications. The first factor is three varieties of green beans (Kutilang, Vima 2, Sampoeng) and the second is five levels of boron fertilization doses (0 kg ha-1, 1,5 kg ha-1, 3,0 kg ha-1, 4,5 kg ha-1, 6,0 kg ha-1). The variables observed are growth, yield and yield components variables. Data were analyzed using analysis of variance and Duncan's test, each at the 5% level. The optimum dose for each variety was obtained through second order (quadratic) regression analysis. The results show that there are differences in the response between the three varieties to boron fertilizer in the variable seed weight per plant. The influence of varieties can be seen independently on all variables, the influence of boron fertilizer has an independent influence on all variables except the number of primary branches. The optimum dose of boron for the kutilang variety is 2.39 kg ha-1, the Vima 2 variety is 3.36 kg ha-1, and Sampoeng, 3.19 kg ha-1.